Peran Inovasi dalam Value Chain di Industri Kelapa Sawit : Studi Kasus di Kabupaten Merauke - Enala, Syahrabudin Husein; Nur Jalal; Hesty Tambajong; Dodhy Hyronimus Ama Longgy (Papsel Journal of Humanities and Policy, 2025)
The palm oil industry plays a strategic role in Indonesia's economy, including in Merauke Regency, which is one of the developing palm oil plantation areas in Papua. However, challenges in production efficiency, environmental sustainability, and competitiveness remain obstacles in the industry's value chain. Innovation in various aspects of the value chain, such as productivity improvement through agricultural technology, processing efficiency, and product diversification based on palm oil, is a key factor in enhancing the industry's competitiveness. This study aims to analyze the role of innovation in the palm oil industry value chain in Merauke Regency by identifying the types of innovations applied and the factors that support or hinder their adoption. The research employs a qualitative approach, using data collection techniques such as in-depth interviews, observations, and document studies. The findings indicate that upstream sector innovations, such as the use of superior seedlings and digital plantation management, have improved productivity and efficiency. Meanwhile, downstream innovations in palm oil processing and value-added product diversification still face challenges, particularly in infrastructure and regulatory aspects. The study's implications suggest that optimizing innovation in the palm oil value chain requires more adaptive policies, increased investment in research and development, and capacity building for human resources. Thus, innovation can serve as a driving force in creating a more competitive, sustainable palm oil industry that contributes to local economic development in Merauke Regency.